Assessment Ideas For Fostering Online Learning Autonomy - Sokhira Linda Vinde Rambe (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2021)
Learning autonomy means learners have to take responsibility in handing their own learning with the help and supervision guided by teachers. Then, selecting types of assessment techniques can be a way to create students’ learning autonomy during the instructional process. Thus, the objective of this study is to determine some techniques of English learning assessment that can foster students’ learning autonomy in online learning environment. Qualitative research was applied as research design done at English Education Department of the Institute for Islamic Studies of Padangsidimpuan. Ten lecturers of English Education Department were chosen purposively as respondents and interview was used as data collection technique. Then, the data were analyzed through qualitative data analysis in which the data were described and elaborated in detail ways. Related to findings, this study found some techniques of English learning assessment that regarded effective to improve students’ independence in online learning i.e. portfolio assessment, discussion and problem solving, essays and summary writing, online presentation, multimedia presentation, mini research, and recording performance task. Finally, this study concluded that there are many assessment techniques to foster students’ online learning autonomy and the promotion of learning autonomy becomes an important aspect to be included in online learning environment.